The Arrogance of Race: Historical Perspectives on Slavery, Racism, and Social Inequality - Hansen, Klaus J. (Labour / Le Travail, 1991)
The article reviews the book, "The Arrogance of Race: Historical Perspectives on Slavery, Racism and Social Inequality," by George M. Fredrickson.
Keywords: ARROGANCE of Race: Historical Perspectives on Slavery; Racism & Social Inequality; The (Book); BOOKS – Reviews; FREDRICKSON; George M.; Nonfiction; Slavery